Educational Aspirations and Inequality: Determinants of High School Students’ Intentions to Pursue Higher Education Across Selected Countries (Global Journal of Human-Social Science, 2025)
Educational aspirations shape students’ life trajectories yet remain unequally distributed across socioeconomic and family contexts. This article investigates determinants of high-school students’ intentions to pursue higher education using 2022 PISA data. A multinomial logit model estimates the effects of individual, family, school, and regional factors across ten countries, covering developed and developing contexts. Students with greater cultural and socioeconomic capital, higher academic performance, stronger family and school support, and clearer vocational goals are more likely to aspire to higher education. Crossnational differences reflect institutional, cultural, and economic variation, with notable contrasts between Latin American countries, Finland, and South Korea. Grounded in Human Capital and Social Reproduction theories, the study advances understanding of how structural inequalities and individual expectations interact in shaping educational aspirations. These findings underscore the importance of targeted public policies and early interventions to ensure social origin does not determine educational opportunities.